2022
DOI: 10.1177/00033197221105747
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Lung Function From Mid-to Late-Life With Central Arterial Stiffness: The Atherosclerosis Risk in Communities Study

Abstract: We investigated the association of lung function at mid-life, later in life, and its 20-year decline, with arterial stiffness later in life. We examined 5720 Atherosclerosis Risk in Communities Study participants who attended Visits 1 (1987-1989) and 5 (2011-2013). Lung function measures were forced expiratory volume in one second (FEV1) and forced vital capacity (FVC), obtained at Visits 1, 2 (1990–1992), and 5. Central artery stiffness (carotid-femoral pulse wave velocity [cfPWV]) was measured at Visit 5. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…6 A causal association could help explain the excess CV morbidity and mortality reported in patients with chronic obstructive pulmonary disease. However, BP and inflammatory state were not tested in a mediation analysis by Peter et al 3 Therefore, causality cannot be confirmed. Alternatively, the association between lung dysfunction and increased arterial stiffness could be non-causal since both arterial and lung function can be affected by an external third factor acting in early life and in the course of life.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…6 A causal association could help explain the excess CV morbidity and mortality reported in patients with chronic obstructive pulmonary disease. However, BP and inflammatory state were not tested in a mediation analysis by Peter et al 3 Therefore, causality cannot be confirmed. Alternatively, the association between lung dysfunction and increased arterial stiffness could be non-causal since both arterial and lung function can be affected by an external third factor acting in early life and in the course of life.…”
mentioning
confidence: 98%
“…A question raised by the results of Peter et al 3 is whether the association between lung and arterial function is causal or not. Lung dysfunction (exposure) could lead to increased arterial stiffness (outcome).…”
mentioning
confidence: 99%
See 3 more Smart Citations